Analisis Kandungan Nitrat dan Nitrit pada Air Tanah di Sekitar Perkebunan Kelapa Sawit - Winny Laura Christina Hutagalung; Rizky Mutia Puteri Rei; Freddy Ilfan (INSOLOGI: Jurnal Sains dan Teknologi, 2022)
The research was conducted on oil palm plantations in Sumber Harapan Village with an area of ​​1,585 hectares of oil palm plantations or 92.66% of the total area of ​​1,710.51 hectares of village. This study was conducted with the aim of knowing the relationship and effect of distance, groundwater level, fertilization dose and time and condition of dug wells on nitrate and nitrite concentrations in the study area and the distribution of nitrate and nitrite concentrations in ground water around oil palm plantations Sumber Harapan Village. Determination of the location of the sample points was carried out using the purposive sampling method. Nitrate and nitrite compound tests were carried out on 15 groundwater sample points using the Palintest 7500 photometer. In the results, 14 units of dug wells (93.33%) are unstandard and 1 unit (6.67%) is following standar based on the Guidelines for Housing and Rural Settlement Development Criteria for PUPR RI number 5 of 2016. The results showed that the highest nitrate concentration was at location S14 at 4.140 mg/l and the lowest nitrate was at location S13 at 0.063 mg/l. The highest nitrite concentration value was at location S4 of 0.028 mg/l and the lowest nitrite was at S14 of 0.000 mg/l. Concentrations of nitrate and nitrite are evenly distributed throughout the study area with a radius of 100 meters from the groundwater sample point. The results showed that the concentration of nitrate and nitrite was still below the quality standard based on the Regulation of the Minister of Health Number 32 of 2017